FIXED POINT THEOREMS FOR RATIONAL TYPE CONTRACTIONS WITH PPF DEPENDENCE IN BANACH SPACES - Saluja, A S (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The aim of this paper is to prove fixed point theorem with PPF dependence for mappings involving - rational type contraction in Razumikhin class. Â Keywords: PPF dependent fixed point, rational type contraction, Razumikhin class. Mathematics Subject Classification: 47H10; 54H25.